HIGH AND LOW ACHIEVERS’ LEARNING STRATEGIES IN READING COMPREHENSION - Iis Nurjanah (Journal of English Education Program (JEEP), 2016)
This study investigates the language learning strategies use in reading comprehension of 20 EFL students with differing reading achievement at the eleventh grade of two senior high schools in Ciamis. Language learning strategy is the way or trick that employed by the learners as an attempt to solve the problem in their learning. Moreover, it makes the learning faster and easier. By administering questionnaire, conducting interview and using Strategy Inventory for Language Learning (SILL), the study analyzes the high and low achievers’ learning strategies in reading comprehension. The results show that the high achievers are dominant in using affective strategies followed by metacognitive, compensation, social, and memory strategies. On the other hand, the low achievers are dominant in using compensation strategies followed by affective, cognitive, social, metacognitive and memory strategies. The findings indicate that different location, condition, and achievement of school do not relate to the use of broad strategy categories as a whole. The results will become useful feedback for the teachers concerning the importance of knowing and understanding how to help their students in applying strategy in their learning, especially in reading comprehension.